Ultra-Processed Food Intake and Sedentary Behavior as Contributing Factors to Overweight and Obesity Among Final-Year Students: A Narrative Review - Keisha Annisa Tadjudin (Yayasan Literasi Sains Indonesia, 2026)
Obesity is becoming increasingly common among university students and may be influenced by frequent consumption of ultra-processed foods (UPFs) and a sedentary lifestyle. This narrative review explores the potential link between these two factors and weight gain in young adults, based on findings from recent studies. UPFs, typically high in calories, added sugars, and unhealthy fats, are often a regular part of students’ diets and contribute to poor overall nutritional quality. Meanwhile, prolonged sedentary behavior, such as extended screen time or studying, is associated with lower energy expenditure and increased body fat. These two habits may interact and further elevate the risk of obesity, although more evidence is needed to confirm a causal relationship. Moreover, academic stress, limited time for physical activity, and the easy accessibility of fast food may worsen the issue. Universities are therefore encouraged to support healthier behaviors through improved nutrition education and physical activity promotion. Helping students adopt better lifestyle choices could contribute to lowering obesity rates and improving their long-term health outcomes.